Hydrodynamics of a pilot plant spray extraction column - Sovilj Milan N. (Acta Periodica Technologica, 2018)
The hydrodynamic characteristics of the liquid-liquid system of toluene-water in a pilot plant spray extraction column were experimentally determined. The experimental data for hydrodynamic characteristics such as the dispersed phase holdup, mean droplet size, and the axial dispersion coefficient were obtained. The dispersed phase superficial velocity had a great influence on toluene holdup. At the same time, a strong effect of the continuous phase superficial velocity on the dispersed phase holdup was evident. The dispersed phase holdup had a tendency to increase when the ratio of the dispersed phase superficial velocity and characteristic velocity increased. The Sauter mean droplet diameter decreased with increasing dispersed phase superficial velocity when the continuous phase superficial velocity remained constant. In contrast, it was not affected by the changes in the continuous phase superficial velocity while the dispersed phase superficial velocity remained constant. It was concluded that the Peclet number increased as a result of an increase of the Reynolds number.